Responsiveness of the Short Warwick Edinburgh Mental Well-Being Scale (SWEMWBS): evaluation a clinical sample - Neha Shah; Mizaya Cader; William P. Andrews; Dilini Wijesekera; Sarah L. Stewart-Brown (Health and Quality of Life Outcomes, 2018)
Abstract Background SWEMWBS is a popular measure of mental wellbeing, shown to be valid in clinical populations. Responsiveness to change has not yet been formally assessed. Methods Analysis of data from a clinical sample of 172 clients undergoing up to 4 sessions of cognitive hypnotherapy. Cohen’s D effect size (ES), Standardised response mean (SRM), probability of change statistic (P^) were used to evaluate whether SWEMWBS detected statistically important changes at the group level. Cohen’s D effect size (ES) and Standard error of measurement (SEM) and were used to evaluate whether SWEMWBS detected statistically important changes at the individual level. Results Mean (SD) SWEMWBS scores increased from baseline to therapy 4 from 19.28 (3.921) to 23.32 (4.873). At group level, using Cohen’s D effect size, improvement ranges from ES = 0.20–1.41 and using SRM, ranged from 0.30–0.88, increasing with number of therapy sessions. (P^) ranged from 0.65–0.8. At individual level, use of Cohens D ES > 0.5 indicated statistically important improvement in 29.9–86.1% cf. 20.1–80.6% using a standard of 2.77 SEM (2.87 points). The lower threshold of 1 SEM (1.03 points) indicated statistically important improvement in 43.0–81.0%. Conclusion SWEMWBS is responsive to change at individual and group level. At individual level a change of between 1 and 3 points meets thresholds for statisticially important change, depending on standard used. Anchor based studies are necessary to confirm that such change represents minimally important change from the perspective of study participants.